2022
DOI: 10.1021/acs.jmedchem.2c00165
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of BMS-986339, a Pharmacologically Differentiated Farnesoid X Receptor Agonist for the Treatment of Nonalcoholic Steatohepatitis

Abstract: While several farnesoid X receptor (FXR) agonists under clinical investigation for the treatment of nonalcoholic steatohepatitis (NASH) have shown beneficial effects, adverse effects such as pruritus and elevation of plasma lipids have limited their clinical efficacy and approvability. Herein, we report the discovery and preclinical evaluation of compound 32 (BMS-986339), a nonbile acid FXR agonist with a pharmacologically distinct profile relative to our previously reported agonist BMS-986318. Compound 32 exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In a recent preclinical study, the BMS-986339, a novel non-bile acid FXR agonist showed potent in vitro and in vivo activation of FXR, with anti-fibrotic efficacy and tissue-selective effects in vivo. The safety of this molecule, however, still requires to be adequately tested in humans [ 257 ].…”
Section: Fxr As a Therapeutic Target?mentioning
confidence: 99%
“…In a recent preclinical study, the BMS-986339, a novel non-bile acid FXR agonist showed potent in vitro and in vivo activation of FXR, with anti-fibrotic efficacy and tissue-selective effects in vivo. The safety of this molecule, however, still requires to be adequately tested in humans [ 257 ].…”
Section: Fxr As a Therapeutic Target?mentioning
confidence: 99%
“…No further attempts to optimize the preparation of 15C were made at this time. An alternative approach could involve bromination of 1,4‐diphenylbicyclo[2.2.2]octane [43] followed by conversion of the resulting 15C to 3’C with MeONa/CuBr in DMF, according to a procedure for a similar compound [44] …”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach could involve bromination of 1,4-diphenylbicyclo[2.2.2]octane [43] followed by conversion of the resulting 15C to 3'C with MeONa/CuBr in DMF, according to a procedure for a similar compound. [44] The requisite 1,4-dibromobicyclo[2.2.2]octane ( 22) was prepared in 55 % from bicyclo[2.2.2]octane-1,4-diol [40] (23) using PBr 3 and polyphosphoric acid (PPA), according to a literature procedure. [45] A similar reaction involving HBr/H 2 SO 4 /ZnBr 2 [23] gave a mixture of mono-and dibromobicyclo[2.2.2]octane in about 1 : 1 ratio.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 , 8 , 9 , 10 , 11 , 12 ]). The interesting feature of the 1,2,4-oxadiazole moiety from a medicinal chemistry viewpoint is its potential coverage of a broad spectrum of therapeutic areas, including oncology [ 13 , 14 , 15 ], immunology [ 16 ], neurology [ 17 , 18 , 19 , 20 ], infectious diseases [ 21 , 22 , 23 , 24 ], metabolism and endocrinology [ 25 , 26 , 27 , 28 ], urology [ 29 , 30 ], gastroenterology [ 31 ], cardiology [ 32 ], rheumatology [ 33 ], and respirology [ 34 ]. Such versatility of the 1,2,4-oxadiazole motif, in our opinion, is due to its recognition as the hydrolytically stable bioisostere of the amide and ester bonds [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%